Development and ultrastructure of the endodermis in the primary root of cork oak (Quercus suber) - Verdaguer, Dolors; Molinas, Marisa (Canadian Journal of Botany, 1997)
The endodermis maturation process was studied in the primary root of the cork oak (Quercus suber L.) with emphasis on the chemical nature of the cell wall and on the possible role of tannins. Tannins were found in endodermal and adjacent cortical cells in all maturation stages. We discuss our findings in relation to the previous literature in other woody and herbaceous species. The results of the histochemical tests showed differences in the aliphatic compounds of the suberin between the Casparian strip suberin and the suberin layer deposited in state II cells. Plasmodesmata were present in radial and tangential walls during the entire maturation process. The significance of plasmodesmata and of the suberin deposition pattern is discussed in relation to apoplastic and symplastic transport in roots. Key words: Casparian strip, endodermis, primary root, suberin, Quercus suber L.
doi: 10.1139/b97-087
Keywords: Casparian strip; endoderrnis; primary root; Quercus suber L.; suberin